Gamma-Delta T Cell Acute Lymphoblastic Leukemia: A Single-Center Experience - Donnellan W; Mineishi S; Wicker J; Paluri R (Global Journal of Cancer Therapy - Peertechz Publications, 2016)
Gamma-delta (γδ) T cell neoplasms are a rare disease entity characterized by an aggressive clinical course [1,2]. The management of these neoplasms associated with high incidence of induction failures and poor clinical outcomes [3]. Here we present two cases of gamma-delta T cell acute lymphoblastic leukemia (γδ T-ALL) successfully treated with chemotherapy and allogeneic stem cell transplant at our institution. We also review the literature and summarize what is known about this disease. In our experience, induction chemotherapy followed by allogeneic stem cell transplantation has been an effective strategy in producing durable remissions.